THE LANDFORMS AND PATTERN OF DEGLACIATION OF THE DRAGON GLACIER, KING GEORGE ISLAND, SOUTH SHETLANDS, ANTARCTICA - Rosa, Kátia Kellem da (Universidade Federal de Pernambuco, 2013)
This paper presents results of an application of the techniques of the landforms mapping for reconstruction of the evolution of the environments of the ice-free in Dragon glacier, Martel Inlet, King George Island, South Shetlands. Reconstructing change of the glacier extension was created through moraine positions mapping and historical satellital images. The geomorphologic mapping generated contributes in identify processes that influence the formation of glacial geomorphology in relation to glacial dynamics and paraglacial modification as aeolian action and debris flow. Furthermore the geomorphical mapping serves as support to monitoring environmental change against the retreat processes as effect of climate variability verified in the study area. This study presented geomorphologic application of the glacier reconstruction modeling method. This approach can be used to validate geomorphologic interpretations of marginal deglaciation.